Magnetic field assisted preparation of PES-Ni@MWCNTs membrane with enhanced permeability and antifouling performance. (March 2020) - Yu, Weiming; Liu, Ying; Shen, Liguo; Xu, Yanchao; Li, Renjie; Sun, Tianyu; Lin, Hongjun
Abstract: Multiple wall carbon nanotubes (MWCNTs), as an excellent material, have been used in various applications including preparation of polymer-MWCNTs composite membranes. However, few reports have combined the magnetic Ni@MWCNTs with polyether sulfone (PES) membrane to improve its antifouling performance to humic acid (HA), sodium alginate (SA), bovine serum albumin (BSA) and yeast (YE) solutions. In this study, the Ni@MWCNTs was generated by immersing MWCNTs into Ni 2+ solution where in-situ reduction reaction was launched by the adsorbed Ag + on MWCNTs. Since the loaded Ni endowed magnetism to MWCNTs, the Ni@MWCNTs can be easily attracted onto the membrane surface by an external magnetic field during the phase inversion process. The morphology measurements confirmed that the Ni@MWCNTs headed out of the PES-Ni@MWCNTs membrane surface. Because the MWCNTs played a role of free channels for water molecules, the composite membrane water flux reached to threefold flux of the pristine membrane. Moreover, the PES-Ni@MWCNTs membranes displayed the obviously enhanced antifouling ability during all the three alternative filtration cycles of water and BSA, SA, YE and HA solutions. In addition, the optimal PES-Ni@MWCNTs membrane demonstrated a flux recovery rate (FRR) of 67.89%, 85.53%, 60.28 and 90.12% for BSA, SA, YE and HA, respectively, which were not only much higher than that of the pristine membrane, but also exhibited significant improvements comparing with the previous studies. Further results of extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) theory indicated that the modified membrane possessed advantageous interaction energies with contaminant molecules over the pristine membrane. Graphical abstract: Image 1 Highlights: Magnetic Ni@MWCNTs were prepared by an in-situ reduction reaction. A novel PES-Ni@MWCNTs membrane was firstly fabricated under an external magnetic field. PES-Ni@MWCNTs membrane displayed FRR of 67.89%, 85.53%, 60.28 and 90.12% for BSA, SA, YE and HA, respectively. The antifouling mechanism was indicated by XDLVO theory.